Impact of low-dose protocols on computed tomography of lung cancer screening on the intrinsic performance metrics: a phantom study - Karim, M.K.A.; Khalidi, M. E.; Chew, M. T.; Kechik, M. M. A.; Mazlan, D.; Ng, K. H. (2023)
Introduction: This research aims to assess the task-based performance of low dose CT lung examination with different acquisition parameters, evaluate the acquisition parameters of lung cancer in low dose CT lung examination, and explore the effect of the iterative reconstruction (IR) algorithm on the image quality of low dose CT for CT lung examination. Methods: This study employed a Catphan 600 to assess the maximum performance of multi-slice CT scanners for radiation therapy planning, utilizing increased sensitometry samples. The CTP404 test module of the Catphan 600 included sensitometry samples of Teflon, Delrin, Acrylic, Polystyrene, LDPE, PMP, Air, and a small water vial. The protocols were divided into three categories: standard, low dose and ultra-low dose. The standard protocol includes a tube voltage of 100 kVp for standard dose computed tomography (SDCT), a pitch of 0.75, detector collimation of 0.60 mm, and a gantry rotation time of 0.33 seconds. The slices were 5 mm thick and reconstructed using a standard reconstruction kernel, for example B80f and 170f, combined with FBP or various IR Results: The low dose group used an acquisition parameter with 100 kVp and a pitch of 0.9, while the standard dose used a pitch of 0.75. The difference in pitch allows for thinner image slices, which improves partial volume averaging and optimizes the (low contrast detectability (LCD). We compared the noise power spectrum (NPS), target transfer function (TTF), and contrast-to-noise ratio (CNR) values for different IR algorithm levels in the low dose group for both acrylic and LDPE inserts. As the IR level increased, the peak value of NPS (HU2 mm2) also increased, with FBP having the highest peak value. Additionally, the NPS spatial frequency decreased with increasing IR level. Conclusions: To sum up, research is being conducted to determine how CT image quality is affected by low dose CT acquisition parameters and IR algorithm. It is essential to adjust IR levels accurately as higher levels can reduce image texture and influence NPS spatial frequency. TTF and CNR are considered the most important performance measures for protocol optimisation as they enhance the contrast and spatial resolution for the background and region of interest.